Transcranial Direct Current Stimulation Modulates Cortical Neuronal Activity in Alzheimer's Disease - Marceglia, Sara; Mrakic-Sposta, Simona; Rosa, Manuela; Ferrucci, Roberta; Mameli, Francesca; Vergari, Maurizio; Arlotti, Mattia; Ruggiero, Fabiana; Scarpini, Elio; Galimberti, Daniela; Barbieri, Sergio; Priori, Alberto (Frontiers in Neuroscience, 2016)
Quantitative electroencephalography (qEEG) showed that Alzheimer’s disease (AD) is characterized by increased theta power, decreased alpha and beta power, and decreased coherence in the alpha and theta band in posterior regions. These abnormalities are thought to be associated with functional disconnections among cortical areas, death of cortical neurons, axonal pathology, and cholinergic deficits. Since transcranial Direct Current Stimulation (tDCS) over the temporo-parietal area is thought to have beneficial effects in patients with AD, in this study we aimed to investigate whether tDCS benefits are related to tDCS-induced changes in cortical activity, as represented by qEEG. A weak anodal current (1.5 mA, 15 min) was delivered bilaterally over the temporal-parietal lobe to 7 subjects with probable AD (Mini-Mental State Examination, MMSE score >20). EEG (21 electrodes, 10-20 international system) was recorded for 5 minutes with eyes closed before (baseline, t0) and 30 minutes after anodal and cathodal tDCS ended (t1). At the same time points, patients performed a Word Recognition Task (WRT) to assess working memory functions. The spectral power and the inter- and intra-hemispheric EEG coherence in different frequency bands (e.g., low frequencies, including delta and theta; high frequencies, including alpha and beta) were calculated for each subject at t0 and t1. tDCS-induced changes in EEG neurophysiological markers were correlated with the performance of patients at the WRT. At baseline, qEEG features in AD patients confirmed that the decreased high frequency power was correlated with lower MMSE. After anodal tDCS, we observed an increase in the high-frequency power in the temporo-parietal area and an increase in the temporo-parieto-occipital coherence that correlated with the improvement at the WRT. In addition, cathodal tDCS produced a non-specific effect of decreased theta power all over the scalp that was not correlated with the clinical observation at the WRT. Our findings disclosed that tDCS induces significant modulations in the cortical EEG activity in AD patients. The abnormal pattern of EEG activity observed in AD during memory processing is partially reversed by applying anodal tDCS, suggesting that anodal tDCS benefits in AD patients during working memory tasks are supported by the modulation of cortical activity.